(untitled) (Academicia Globe: Inderscience Research, 2022)
This article provides a solution to creative problems in the subject "Technical creativity and design". Methods and techniques for the development of cognitive activity in solving creative problems are given. Using the data given in the article, each teacher can contribute to the development of the technical creativity of students. Using the data given in the article, each teacher can contribute to the development of students’ technical creativity. The principle of figurative comparison, based on the existing knowledge and skills of students, includes questions to determine the true meaning of each word and sentence. At the practical classes on the subject "Technical Creativity and Design" there was a conversation about how teachers can independently perform technical tasks.